Between seas and continents: aspects of the scientific career of Hermann Von Ihering, 1850-1930 - Lopes, Maria Margaret (2014)
This paper covers some periods in Hermann von Ihering’s scientific trajectory: his training in zoology in Germany and Naples, his international activities based in Brazil, and his return to Germany. It deals with aspects of the formulation of his theories on land bridges. It focuses on the network of contacts he maintained with German émigrés like himself, and primarily with Florentino Ameghino, which allowed him to interact in international scientific circles. It mentions excerpts of his letters and his publications in the periods when he began corresponding with Ameghino (1890), when he travelled to Europe in search of support for his theories (1907), and when he published his book on the history of the Atlantic Ocean (1927).